IOT-Based Smart Speed Controller for E-Vehicles - G, Manimala; V, Swarna Lakshme; R, Kaviya; S, Tanuja (2023 Intelligent Computing and Control for Engineering and Business Systems (ICCEBS), 2023)
The rapid growth of electric vehicles (EVs) necessitates innovations in safety and efficiency. This paper introduces a smart speed controller system for EVs, combining LiDAR technology, traffic light data, and real-time communication to enhance vehicle safety and traffic flow. By integrating Arduino microcontrollers and RF components, the system dynamically adjusts vehicle speed based on detected nearby vehicles and traffic light signals, promoting both safety and energy efficiency in the e-vehicles.